On The Realization of Low/High Frequency CCII+ Based Oscillators Employing Grounded Resistors and Lossy Capacitors - Muhammad Taher Abuelma'atti; Muhammad Haroon Khan (Active and Passive Electronic Components)
New RC oscillator circuits are presented. Each circuit uses two second-generation positive current-conveyors, three grounded capacitors and four grounded resistors. The circuits enjoy independent control of the frequency and the condition of oscillation and are very attractive for integration. The circuits can realize high and low frequencies of oscillation. Simulation results are included.